Analysis of Consumer Behavior on Design and Quality Preferences for Bonas Jaya Furniture Cabinet Products in Central Lampung - Ninda Sali Agusta; M. Oktavianur (The Eastasouth Journal of Social Science and Humanities, 2026)
This study aims to analyze consumer behavior towards design and quality preferences for Bonas Jaya Furniture cabinets in Central Lampung. The increasingly competitive development of the furniture industry requires businesses, particularly MSMEs, to understand consumer behavior patterns in determining purchasing decisions. This study uses a qualitative approach with descriptive methods. Data were obtained through in-depth interviews with internal informants consisting of business owners, production employees, and marketing staff, as well as external informants in the form of consumers who have used the cabinet products. Data analysis was conducted by examining the stages of consumer behavior, namely need awareness, information search, alternative evaluation, purchase decision, and post-purchase behavior. The results show that consumer preference for Bonas Jaya cabinets is significantly influenced by the suitability of the design to the living space conditions and product quality, including materials, workmanship, and finishing results. Consumers tend to carry out the decision-making process rationally and planned, supported by trust and transparency of information from the business. Positive post-purchase behavior is reflected in the level of consumer satisfaction and the tendency to make repeat purchases and provide recommendations to others. This study is expected to serve as a reference for local furniture businesses in designing product development strategies oriented to consumer needs and preferences..